Thermal limits of leaf metabolism across biomes. (14th October 2016) - O'sullivan, Odhran S.; Heskel, Mary A.; Reich, Peter B.; Tjoelker, Mark G.; Weerasinghe, Lasantha K.; Penillard, Aurore; Zhu, Lingling; Egerton, John J. G.; Bloomfield, Keith J.; Creek, Danielle; Bahar, Nur H. A.; Griffin, Kevin L.; et al.
Abstract: High‐temperature tolerance in plants is important in a warming world, with extreme heat waves predicted to increase in frequency and duration, potentially leading to lethal heating of leaves. Global patterns of high‐temperature tolerance are documented in animals, but generally not in plants, limiting our ability to assess risks associated with climate warming. To assess whether there are global patterns in high‐temperature tolerance of leaf metabolism, we quantified T crit (high temperature where minimal chlorophyll a fluorescence rises rapidly and thus photosystem II is disrupted) and T max (temperature where leaf respiration in darkness is maximal, beyond which respiratory function rapidly declines) in upper canopy leaves of 218 plant species spanning seven biomes. Mean site‐based T crit values ranged from 41.5 °C in the Alaskan arctic to 50.8 °C in lowland tropical rainforests of Peruvian Amazon. For T max, the equivalent values were 51.0 and 60.6 °C in the Arctic and Amazon, respectively. T crit and T max followed similar biogeographic patterns, increasing linearly ( ˜ 8 °C) from polar to equatorial regions. Such increases in high‐temperature tolerance are much less than expected based on the 20 °C span in high‐temperature extremes across the globe. Moreover, with only modest high‐temperature tolerance despite high summer temperature extremes, species in mid‐latitude (~20–50°) regions have the narrowest thermal safety margins in upper canopy leaves; these regions are at the greatest risk of damage due to extreme heat‐wave events, especially under conditions when leaf temperatures are further elevated by a lack of transpirational cooling. Using predicted heat‐wave events for 2050 and accounting for possible thermal acclimation of T crit and T max, we also found that these safety margins could shrink in a warmer world, as rising temperatures are likely to exceed thermal tolerance limits. Thus, increasing numbers of species in many biomes may be at risk as heat‐wave events become more severe with climate change.